Analisis Yuridis Tindak Pidana Carding Sebagai Bentuk Kejahatan Transnasional - Larif, Choirul Mustika Al Hafizhil; Mulyanto, Rudi; Martiasari, Andin (Fakultas Hukum Universitas 17 Agustus 1945 Banyuwangi, 2024)
Carding is a crime where someone steals another person's credit card number and uses it for online transactions. Carding has become a type of transnational crime. Transnational crime refers to criminal acts carried out across countries by individuals, groups, or syndicates using cross-border networks for specific purposes and gains. The type of research used is normative legal research and it employs normative case studies. In this research, the approaches used are the legislative approach and the analytical approach. The research results show that to address transnational crimes such as Carding, Indonesia needs to have regulations that meet international standards. Proving the crime of Carding requires a special approach due to the digital and transnational nature of this crime. Proof in the context of criminal law must meet certain standards to ensure that justice is upheld.